PTU-022 Caecal location is associated with increased lesion recurrence following endoscopic mucosal resection of large non-pedunculated colorectal polyps. (22nd June 2015) - Chattree, A; Rutter, MD
Abstract : Introduction: Large caecal polyps over 2 cm in size are considered amongst the most complex lesions to achieve successful endoscopic resection, with recent data suggesting a significantly increased risk of post procedure bleeding and perforation associated with their endoscopic removal compared with elsewhere in the colon. 1, 2 There is however a paucity of data assessing whether caecal location affects successful (R0 ) clearance of lesions. Method: Retrospective analysis was conducted on large non-pedunculated colorectal polyps (LNPCPs) managed with endoscopic mucosal resection in the North East Bowel Cancer Screening Programme (BCSP) between 2011–12. A comparison of 12 month recurrence rates, an internationally recognised marker of treatment success, 3 was made between caecal and non-caecal LNPCP groups. Statistical analysis was performed using the chi-squared test. Results: A total of 135 lesions were identified, with 12 month recurrence identified in 8.1% of cases. Caecal location demonstrated a strongly significant association with recurrence compared with non-caecal location (27.8% vs 5.1%, p = 0.007) Conclusion: Caecal location was associated with over a 5-fold increase (28.7% vs 5.1%) in the incidence of 12 month recurrence. The results from this series confirm the increased technical demands associated with the endoscopic resection of caecal LNPCPs, especially considering our study involved experienced BCSP endoscopists. In view of the increased risk of endoscopic treatment failure, in addition to the established increased risk of adverse endoscopic events, we feel that caecal LNPCPs may benefit from multidisciplinary discussion and should only be managed by experienced clinicians. Disclosure of interest: None Declared. References: Rutter MD, Nickerson C, Rees CJ, et al . Risk factors for adverse events related to polypectomy in the English Bowel Cancer Screening Programme. Endoscopy 2014;46:90–7 Metz AJ, Bourke MJ, Moss A, et al . Factors that predict bleeding following endoscopic mucosal resection of large colonic lesions. Endoscopy 2011;43:506–11 Moss A, Bourke MJ, Williams SJ, et al . Endoscopic mucosal resection outcomes and prediction of submucosal cancer from advanced colonic mucosal neoplasia. Gastroenterology 2011;140:1909–18